A sampling optimization analysis of soil‐bugs diversity (Crustacea, Isopoda, Oniscidea). Issue 1 (17th December 2015) - Messina, Giuseppina; Cazzolla Gatti, Roberto; Droutsa, Angeliki; Barchitta, Martina; Pezzino, Elisa; Agodi, Antonella; Lombardo, Bianca Maria
Abstract: Biological diversity analysis is among the most informative approaches to describe communities and regional species compositions. Soil ecosystems include large numbers of invertebrates, among which soil bugs (Crustacea, Isopoda, Oniscidea) play significant ecological roles. The aim of this study was to provide advices to optimize the sampling effort, to efficiently monitor the diversity of this taxon, to analyze its seasonal patterns of species composition, and ultimately to understand better the coexistence of so many species over a relatively small area. Terrestrial isopods were collected at the Natural Reserve "Saline di Trapani e Paceco" (Italy), using pitfall traps monthly monitored over 2 years. We analyzed parameters of α ‐ and β ‐diversity and calculated a number of indexes and measures to disentangle diversity patterns. We also used various approaches to analyze changes in biodiversity over time, such as distributions of species abundances and accumulation and rarefaction curves. As concerns species richness and total abundance of individuals, spring resulted the best season to monitor Isopoda, to reduce sampling efforts, and to save resources without losing information, while in both years abundances were maximum between summer and autumn. This suggests that evaluations of β ‐diversity are maximized if samples are first collected during the spring and then between summer and autumn. Sampling during these coupled seasons allows to collect a number of species close to the γ ‐diversity (24 species) of the area. Finally, our results show that seasonal shifts in community composition (i.e., dynamic fluctuations in species abundances during the four seasons) may minimize competitive interactions, contribute to stabilize total abundances, and allow the coexistence of phylogenetically close species within the ecosystem. Abstract : The aim of the present methodological study is to provide advices in order to optimize the sampling effort, to efficiently monitor the diversity of this taxon and to better analyse the seasonal patterns of species composition in order to understand the coexistence of many species in a relative small area. We used different approaches to analyse changes in biodiversity over time, such as species‐abundances distribution and accumulation and rarefaction curves. Our results show that seasonal shifts in isopods community composition seem to minimize competitive interactions, increase biodiversity, help stabilize total abundance and allow the coexistence of close species in the ecosystem.